Late Mesozoic transition from Andean‐type to Western Pacific‐type of the East China continental margin—Is the East China Sea basement an allochthonous terrain?. (20th October 2017) - Ding, Weiwei; Li, Jiabiao; Wu, Zhaocai; Li, Sanzhong; Lin, Xiubin
Abstract : Geophysical features and crustal structure of the East China Sea basement were revealed based on geophysical inversion analysis with recent gravity and magnetic data. Our results show great differences between the East China Sea continental shelf basins and the Zhemin Volcanic Belt in the coastal South China Block with respect to geophysical features and crustal structures. These areas are separated by distinct geophysical and crustal changes, approximately along a line 100 km from the coastline of China. We hypothesize that the East China Sea basement is a buoyant allochthon in the Palaeo‐Pacific Plate, and that the East China margin was an Andean‐type active continental margin until the collision of the East China Sea basement with the South China Block in the Late Cretaceous, which jammed the Late Cretaceous Trench, terminating the subduction and the related granitoid magmatism. The East China continental margin was dominated by dextral transtension with limited magmatism due to the NNW‐trend motion of the Palaeo‐Pacific Plate with a reduced convergence rate until the Middle Eocene. The renewed westward subduction of the present‐day Pacific Plate replaced the East China Andean‐type continental margin with a Western Pacific‐type one. The detailed reconstructed tectonic model for the East China Sea since the Mesozoic is presented in this paper.